Gold-silica quantum rattles for multimodal imaging and therapy - Hembury,M; Chiappini,C; Bertazzo,S; Kalber,TL; Drisko,GL; Ogunlade,O; Walker-Samuel,S; Krishna,KS; Jumeaux,C; Beard,P; Kumar,CSSR; Porter,AE; et al. (Proceedings of the National Academy of Sciences, 2015)
Gold quantum dots exhibit distinctive optical and magnetic behaviors compared with larger gold nanoparticles. However, their unfavorable interaction with living systems and lack of stability in aqueous solvents has so far prevented their adoption in biology and medicine. Here, a simple synthetic pathway integrates gold quantum dots within a mesoporous silica shell, alongside larger gold nanoparticles within the shell’s central cavity. This “quantum rattle” structure is stable in aqueous solutions, does not elicit cell toxicity, preserves the attractive near-infrared photonics and paramagnetism of gold quantum dots, and enhances the drug-carrier performance of the silica shell. In vivo, the quantum rattles reduced tumor burden in a single course of photothermal therapy while coupling three complementary imaging modalities: near-infrared fluorescence, photoacoustic, and magnetic resonance imaging. The incorporation of gold within the quantum rattles significantly enhanced the drug-carrier performance of the silica shell. This innovative material design based on the mutually beneficial interaction of gold and silica introduces the use of gold quantum dots for imaging and therapeutic applications.